Pemberdayaan Kelompok Guru Matematika Menerjemahkan Sumber Teks Penalaran Tingkat Tinggi Berbahasa Inggris dengan Google Translate Berbasis Android di Kabupaten Soppeng - Rukli Rukli; Syamsiarna Nappu (Publikasi Pendidikan, 2022)
English is the world's social language, but teachers still have limitations, especially in translating English texts. The purpose of the service is to provide counselling, training and then assistance for groups of teachers who are involved in the mathematics teacher consultations. The activity involved 28 mathematics teachers as delegates for each school or madrasa in Soppeng Regency. The activity was carried out on two days from 08.00 to 16.00 WITA. Each stage is carried out pre-test and post-test. Data analysis used percentages and paired t-tests with a significance level of 0.05. The results of the service show that 1) the participants' gestures before and after the activity have improved in a better direction, 2) the participants' understanding of translating text in the form of words, syllables, sentences and paragraphs has increased, 3) the skills of participants in translating English texts have increased by an average of 80%, 4 ) there was a significant difference in the improvement before and after counselling, training, and teacher assistance in translating high-level reasoning English text sources. Therefore, improving the ability and skills of translating English texts can use three stages, namely counselling, training and then assistance using text sources from international journals or international standard mathematics questions.